2000
DOI: 10.1016/s0895-7061(00)01188-2
|View full text |Cite
|
Sign up to set email alerts
|

 2-Adrenergic receptor polymorphisms at codon 16, cardiovascular phenotypes and essential hypertension in whites and African Americans

Abstract: Beta2-adrenergic receptors (beta2-AR) contribute to cardiovascular regulation by influencing several functions and previous studies suggest that a decreased function of the beta2-AR may be involved in essential hypertension. Beta2-AR are polymorphic and certain polymorphisms of these receptors are of functional importance. We focus here on the Arg16-->Gly16 beta2-AR polymorphism, which shows enhanced agonist-promoted downregulation of the receptor and which, in two recent studies, yielded opposite results in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]27,28 Of the 19 eligible articles, the study of Gu et al 28 was replaced by their earlier report, 10 as these two articles reported the same data. Wu et al 5 provided data on two Chinese minorities, the Hani and Yi, residents of the remote rural area of Yunnan, China.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]27,28 Of the 19 eligible articles, the study of Gu et al 28 was replaced by their earlier report, 10 as these two articles reported the same data. Wu et al 5 provided data on two Chinese minorities, the Hani and Yi, residents of the remote rural area of Yunnan, China.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…29 The population of the two minorities was also grouped in to Asian. 30 Tang et al, 27 Herrmann et al 18 and Xie et al 14 provided data on two ethnicities: Caucasian American and AfricanAmerican. The genotyping data of the normotensive controls in the population Caucasian-American in Tang et al 27 (P HWE ¼0.048), and the African-American control subjects studied in Herrmann et al 18 (P HWE ¼0.027) deviated from HWE.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…92 However, other studies have failed to detect any association between the Arg16Gly and Gln27Glu polymorphisms and cardiac dimensions. [95][96][97] These studies did not investigate the role of the Thr164Ile variant.…”
Section: ␤ 1 -Adrenergic Receptor Polymorphismsmentioning
confidence: 99%